2014
DOI: 10.1021/ma500737z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Structural Analysis of Solution-Grown Polyacrylonitrile-co-Methacrylic Acid (PAN-co-MAA) Single Crystals

Abstract: To date studies regarding the growth and characterization of polyacrylonitrile (PAN)-based polymer single crystals have been limited. Polyacrylonitrile-co-methacrylic acid (PAN-co-MAA) was used in this work, which outlines the conditions for three major types of solution-grown crystals. Electron microscopy and diffraction are used to provide a comprehensive study for chain arrangement and growth characteristics for all crystal morphologies. The three major morphological types included polyhedral and polygonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The modulus value for the interphase region is based on the assumption that the interphase polymer consists of highly ordered (i.e., crystalline and/or constrained state) chains. Previous work has shown that in the near vicinity of the nC fillers, the polymer chains tend to be highly oriented and aligned in fiber composites . The proximity of the filler and polymer chains at the interphase region also reduces the chain motion, and this phenomenon can be probed experimentally using dynamic mechanical analysis (DMA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The modulus value for the interphase region is based on the assumption that the interphase polymer consists of highly ordered (i.e., crystalline and/or constrained state) chains. Previous work has shown that in the near vicinity of the nC fillers, the polymer chains tend to be highly oriented and aligned in fiber composites . The proximity of the filler and polymer chains at the interphase region also reduces the chain motion, and this phenomenon can be probed experimentally using dynamic mechanical analysis (DMA).…”
Section: Resultsmentioning
confidence: 99%
“…It was recognized from previous studies that the polymer chains in the near vicinity of the nC filler exhibit conformational distinctions from the bulk matrix . These regions form as a result of interfacial polymer‐nC interactions and lead to the formation of interphase zones in the composite . Effective interfacial interactions and stress transfer between the nanofiller and polymer are also essential for improved mechanical performance in the composite .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed increase in tensile strength and Young's modulus with increasing TRGO content may be explained by the fact that the PVA‐ g ‐PAN chains in the near vicinity of the TRGO exhibit conformational distinctions from the bulk matrix . These regions are formed as a result of interfacial (PVA‐ g ‐PAN)–TRGO interactions and lead to the formation of interface zones in the nanocomposite . These developed zones enable effective interracial interaction and stress transfer between the grafted copolymer and TRGO thus improving the mechanical performance of the materials.…”
Section: Resutls and Discussionmentioning
confidence: 99%
“…Therefore filler dispersion and/or distribution non-uniformity are expected to play the dominant role in this property trend. Since the nC can affect polymer chain arrangement due to interactions between both components, 6,21,28 these interfacial interactions lead to the formation of an ordered interphase region. The presence of this interphase region is known to contribute greatly to the mechanical performance of the composite.…”
Section: Structure-property Relationshipmentioning
confidence: 99%